METHOD AND DEVICE FOR INCREASING THE OPTICAL TRANSPARENCY OF REGIONS OF A TISSUE SAMPLE (2014)
A method for increasing the optical transparency of regions of a tissue sample is proposed, in which the tissue sample is introduced into a process chamber and is infiltrated in the process chamber with at least one process fluid, and in which a removal of light-scattering structures in the tissue sample is carried out. The method encompasses monitoring the optical transparency of the tissue sample, at least during a clearing time period in which the tissue sample is introduced into the process chamber and in which the removal of the light-scattering structures in the tissue sample is carried out, by means of an optical transparency measuring arrangement associated with the process chamber. An apparatus for carrying out the method is also a subject of the invention.